Impact of critical chain project management and product portfolio management on new product development performance - Luiz, Octaviano Rojas [UNESP]; de Souza, Fernando Bernardi [UNESP]; Luiz, João Victor Rojas [UNESP]; Jugend, Daniel [UNESP]; Salgado, Manoel Henrique [UNESP]; da Silva, Sergio Luis (Emerald, 2019)
Purpose: This study aims to analyze the relationship between the adherence to critical chain project management (CCPM) practices and the new product development performance, in terms of the results of product development programs and product portfolio management (PPM). Design/methodology/approach: A survey was conducted with 79 innovative companies operating in Brazil. Data were analyzed using correlation analysis and non-parametric tests. Findings: Significant and positive correlations were found between CCPM adoption and the performance factors proposed. The adoption of CCPM offered stronger correlation with PPM performance than with the adoption of traditional methods. The results further indicate a possible indirect contribution of CCPM practices to the product development program by means of PPM improvement. Originality/value: This study deepens the knowledge of the joint study between project management and new product development, by bringing empirical evidence that the adoption of specific practices suggested by CCPM is used by organizations with superior performance. Moreover, the results broaden CCPM literature by attesting that companies do not necessarily have to apply the CCPM approach in a formal and explicit way to obtain the performance results given. The analyses still have practical value when indicating which CCPM practices should be prioritized by managers seeking high performance in PPM.
Keywords: Critical chain; NPD performance; Product portfolio; Survey; Theory of constraints